CARDIOVASCULAR DISEASES AT GOUT - Kondratiuk, V. Ye.; Berzin, O.V. (The Ukrainian Scientific Medical Youth Journal, 2018)
The article covers data on the study of the main risk factors and the search for prognostic indicators of cardiovascular risk in gout, a modern understanding of the main mechanisms of influencing the risk of cardiovascular diseases. Data on the efficacy and safety of anti-rheumatic therapy in gout from the point of view of cardiovascular risk are presented.